El uso de la paja toquilla como material de diseño de interiores para fortalecer la identidad ecuatoriana - Ibañez Cedeño, Karina Elizabeth (2015)
This titling project is the use of straw scarf as a decorative element in the wall covering and furniture to strengthen Ecuadorian identity, because there is the opportunity to conduct business by the availability of raw material as it is the toquilla straw this being typical of Ecuador, and labor very willing to use in the decorative sector, but within the same proposal within the market has not been exploited because it has been used to cap straw for making the famous straw hats, leaving the door open to develop new designs for interior decoration. This study aims at demonstrating the feasibility of running through an analysis environment through market research where you can check the acceptance of these decorative attachments with the straw scarf, look for a marketing plan and an adequate financial study according to market to be obtained and project implementation to boost the economy of the country developing a new sector…….